Genetic Diversity in Gossypium genus - Abdurakhmonov, Ibrokhim Y.; Buriev, Zabardast T.; Shermatov, Shukhrat E.; Abdullaev, Alisher A.; Urmonov, Khurshid; Kushanov, Fakhriddin; Egamberdiev, Sharof S.; Shapulatov, Umid; Abdukarimov, Abdusttor; Saha, Sukumar; Jenkins, Johnnie N.; Kohel, Russell J.; et al. (IntechOpen, 2012)
None